Aligning Mercury Governance With Livelihoods, Legal Frameworks, and Religious Norms: Evidence from Indonesia’s ASGM - Amanda Adelina Harun; Vanessa Veronica; Fenty U. Puluhulawa (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to examine the health impacts of mercury exposure on miners and communities, analyse patterns of regulatory compliance in the context of largely informal mining, and evaluate the effectiveness of policies and legal instruments designed to reduce mercury use and mitigate environmental impacts. This study synthesises toxicological and biomonitoring evidence, community-based qualitative studies on practices and risk perceptions, and regulatory analysis in relation to international obligations. Results show that mercury biomarkers remain persistently high and there are neurological impacts on exposed populations, while informality limits oversight and weakens compliance. Interventions focused on enforcement often trigger displacement of activities (mining), rather than changes to more sustainable extraction practices. Policy effectiveness increases when regulations are combined with livelihood-sensitive supporting factors, including cooperative-based formalisation, access to financing and training, and technological transition through integrated governance. The study proposes a governance-livelihood-Islamic norm model and a compliance architecture aligned with maqasid al-sharia.